RISIKO MODERNISASI DALAM MENCIPTAKAN LAPANGAN PEKERJAAN - Qoriana Nur Iffah; Shofia Dwi Nurianti (Journal of Management and Social Sciences, 2023)
Modernity is one of the reasons for humans to adapt to be better than previous lives. Technology that is growing rapidly makes the development of industries. But it has not been widely seen that the industry can create social risks. Starting from the work environment is not conducive, employment is getting less, to gender inequality in work. In the industry, there is also often an imbalance in labor wages. Where workers become victims of losses from risks created in an industry. Giddens thought that in the modern era the world would be uncontrollable. It can be seen that industrialization is growing and progressing continuously. That's why the risks that will be accepted cannot be avoided by society in this modern era.